2020
DOI: 10.1021/acs.jpcb.0c02586
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Structures of Tetraethylammonium Bromide and Tetrafluoroborate in Aqueous Binary Solvents with Ethanol, Trifluoroethanol, and Acetonitrile

Abstract: The solvation structures of tetraethylammonium bromide and tetrafluoroborate (TEABr and TEABF 4 ) in aqueous binary solvents with ethanol (EtOH), 2,2,2trifluoroethanol (TFE), and acetonitrile (AN) have been clarified by molecular dynamics (MD) simulations. In addition, 1 H and 13 C NMR chemical shifts of the H and C atoms within TEA + in the binary solvents have been measured as a function of the mole fraction of the organic solvent, x OS . The variations of the chemical shifts with an increase in x OS were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 83 publications
1
8
0
Order By: Relevance
“…This force-field combination provides thermodynamical, structural, and dynamical properties which are in good agreement with the literature. 16,34,38,39,42,80,84,127,128 Fig. S1 of ESI‡ shows an example of such agreements, where the present isothermal compressibility data of ethanol/water mixture agree with the literature.…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…This force-field combination provides thermodynamical, structural, and dynamical properties which are in good agreement with the literature. 16,34,38,39,42,80,84,127,128 Fig. S1 of ESI‡ shows an example of such agreements, where the present isothermal compressibility data of ethanol/water mixture agree with the literature.…”
Section: Methodssupporting
confidence: 88%
“…The molecular diffusion in the mixture goes through a minimum at the alcohol mole fraction x B 0.2, while the viscosity reaches the maximum. 3,4,10,19,[26][27][28][41][42][43][44][45][80][81][82][83][84][85][86] Experiments have shown that the above non-monotonicity is enhanced with decreasing temperature. 24,25,[27][28][29][30][31][32][33] The water/methanol binary mixture also shows a similar non-monotonic composition dependence of diffusion and viscosity coefficients with the extrema at the equimolar mixture.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to electrolytes, their solvation in alcohols and aqueous alcohol solutions are of great significance in many industrial and natural processes [ 22 , 23 , 24 ]. So, the mixtures of alcohols with organic or inorganic salts have been vastly investigated, mostly focusing on understanding the physicochemical properties of the systems [ 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Of particular interest, it has been reported that the dissolution of some salts in certain alcohols in appropriate molar ratios leads to a significant drop in freezing points with respect to the composing pure components, forming the neoteric class of solvents coined as deep eutectic solvents (DESs) [ 23 , 24 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…But, when it comes to the salt-EtOH/aqueous EtOH solutions, there are only a few studies. It has been proposed that in the dissolution process of inorganic salts in ethanol (EtOH) and its derivative, it is the electrostatic force between the dissociated ions and solvent molecules that governs the solvation [ 33 ]. Moreover, alcohols are expected to form solvation structures around the dissociated ions by forming H-bonds [ 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…have been reported to signi cantly in uence the arrangements of molecules in molecular crystals [9][10][11] , photophysical 12 and solvation properties 13 . Several reported studies aimed at understanding the nature of these interactions, including approaches based on statistical analysis 14 , energy calculations 14 , crystal structure analysis 15 and charge-density analysis 16 .…”
Section: Introductionmentioning
confidence: 99%